LIGHT/TNFSF14 regulates estrogen deficiency‐induced bone loss. Issue 4 (25th February 2020) - Brunetti, Giacomina; Storlino, Giuseppina; Oranger, Angela; Colaianni, Graziana; Faienza, Maria F; Ingravallo, Giuseppe; Di Comite, Mariasevera; Reseland, Janne E; Celi, Monica; Tarantino, Umberto; Passeri, Giovanni; Ware, Carl F; et al.
Abstract: Bone loss induced by ovariectomy is due to the direct activity on bone cells and mesenchymal cells and to the dysregulated activity of bone marrow cells, including immune cells and stromal cells, but the underlying mechanisms are not completely known. Here, we demonstrate that ovariectomy induces the T‐cell co‐stimulatory cytokine LIGHT, which stimulates both osteoblastogenesis and osteoclastogenesis by modulating osteoclastogenic cytokine expression, including TNF, osteoprotegerin, and the receptor activator of nuclear factor‐κB ligand (RANKL). Predictably, LIGHT‐deficient ( Tnfsf14 −/− ) mice are protected from ovariectomy‐dependent bone loss, whereas trabecular bone mass increases in mice deficient in both LIGHT and T and B lymphocytes ( Rag −/− Tnfsf14 −/− ) and is associated with an inversion of the TNF and RANKL/OPG ratio. Furthermore, women with postmenopausal osteoporosis display high levels of LIGHT in circulating T cells and monocytes. Taken together, these results indicate that LIGHT mediates bone loss induced by ovariectomy, suggesting that patients with postmenopausal osteoporosis may benefit from LIGHT antagonism. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.